PENGARUH OPINI AUDIT, RASIO LIKUIDITAS DAN NILAI DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - simamora, Samuel fernando; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2022)
Banking stock prices during the last 5 years experienced fluctuating stock prices but overall the average decreased by -8% which was probably due to the auditor's opinion, liquidity and dividend value. The purpose of this research is to see the effect of audit opinion, liquidity and dividend value partially or simultaneously on the decline in stock prices in banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. the data in this study is quantitative, the source of the data in this study is secondary data with SPSS 22 analysis, the data collection technique in this study is by doing documentation, namely downloading the company's financial statements. The tests carried out are classical assumption tests, multiple linear regression tests and also tests hypothesis with t test and f test. The sample in this study is included in the type of purposive sampling. Partially, the results show that audit has no partial effect on stock prices with a value of (0.945 > 0.05), liquidity does not partially affect stock prices with a value (0.157 > 0.05), dividend values ​​partially affect stock prices with a value of (0.00 < 0.05), audit opinion, liquidity and value simultaneously affect stock prices with a value (0.00 < 0.05). In conclusion, audit opinion has no partial effect on stock prices or H1 is rejected, liquidity does not partially affect stock prices or H2 is rejected, dividend value has a partial effect on stock prices or H3 is accepted, audit opinion, liquidity and dividends have a simultaneous effect on prices. banking sector companies whose shares are listed on the Indonesia Stock Exchange in 2017-2021 or H4 are accepted.